Innerwear design for selected adolescents females wearing a Milwaukee brace - Cobol, Bernice Gwen M. (UP College of Home Economics, 2012)
ABSTRACT The study aimed to propose an innerwear design for selected females aged 12-18 years old wearing an orthopaedic Milwaukee back brace. Specifically, the study determined the physical needs, the daily activities, problems and concerns in clothing of the selected females wearing Milwaukee back braces. This is a descriptive research using the survey method. The researcher interviewed 25 respondents purposively selected with the endorsement of the rehabilitation team from the Philippine Orthopaedic Center . The data gathered were tabulated and presented with the use of formal statistical tables through frequency distribution. The results of the study showed that most respondents were being corrected for 34-40 degree of spinal curvature and wore their braces for 20-24 hours a day. Majority have difficulty with dressing and undressing and almost fifty percent of the respondents are dependent of their mothers. Most of them experienced skin irritation. The respondents reported fitting problems on their innerwear specifically on the chest area. Considering the survey results, innerwear was designs with functional features suited for adolescent females wearing Milwaukee Brace were proposed.